Peer Victimization and Life Satisfaction: The Influence of Teacher and Peer Support [Victimización de Pares y Satisfacción Con la Vida: La Influencia del Apoyo de Profesores y Compañeros de la Escuela] - Bilbao-Ramirez, M (Pontificia Universidad Catolica de Chile, 2016)
Violence among peers has a negative effect on students mental health. The literature indicates that life satisfaction is one of the factors on which peer violence could have a major effect. Nevertheless, some factors may attenuate this negative impact. This study analyzed the influence of teacher and peer support on the relation between students peer victimization and life satisfaction. The sample included 5,527 students from grades 4 through 8 attending municipal schools in one district of the Region of Valparaíso, Chile. Using self-report questionnaires taken from the survey "Coexistence in my School", whose data was analyzed with structural equation modeling, it was observed that teacher social support has a greater effect than peer social support as a mediator in the inverse relationship between students peer victimization and life satisfaction. These findings are discussed in terms of the mediating role of teachers in reducing the effects of peer victimization. © 2016 by Psykhe.